2012
DOI: 10.1158/1078-0432.ccr-12-1420
|View full text |Cite
|
Sign up to set email alerts
|

miR-187 Is an Independent Prognostic Factor in Breast Cancer and Confers Increased Invasive PotentialIn Vitro

Abstract: Purpose: Here, we describe an integrated bioinformatics, functional analysis, and translational pathology approach to identify novel miRNAs involved in breast cancer progression.Experimental Design: Coinertia analysis (CIA) was used to combine a database of predicted miRNA target sites and gene expression data. Using two independent breast cancer cohorts, CIA was combined with correspondence analysis and between group analysis to produce a ranked list of miRNAs associated with disease progression. Ectopic expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 48 publications
3
57
0
Order By: Relevance
“…Studies have implicated miR-187 activity in the development of various types of tumors (5,17,18); however, its role in DLBCL has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have implicated miR-187 activity in the development of various types of tumors (5,17,18); however, its role in DLBCL has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and colleagues previously demonstrated that miR-187 is decreased in taxol-resistant ovarian cell lines (29), supporting the data presented here. However, in breast cancer cells, miR-187 was demonstrated to have no effect on sensitivity to tamoxifen or fulvestrant (30). These conflicting data may be due to the tumor-and/or tissue-specific function of miR-187 or may result from the differing modes of action of these cytotoxic agents.…”
Section: C3 Is Altered In Pretreatment Eac Tumors From Nonrespondersmentioning
confidence: 99%
“…Expression levels of a number of miRNAs, which are either positively or inversely associated with metastatic status, disease-free time and overall survival of breast cancer patients have been identified [225][226][227][228][229][230][231][232][233][234][235][236][237][238][239][240] and are detailed in Table 3. The most relevant miRNA with prognostic value in breast cancer is miR-210, the aforementioned oncogenic miRNA implicated in the DCIS-to-IDC transition.…”
Section: Translational Implications Of Ncrnas In Breast Cancermentioning
confidence: 99%